The Efficiency of Parasitoid Cotesia sesamaie (Hymenoptera Braconidae) to Control the Larvae of Tarucus rosacea In Al-Diwaniyah City - Mohammed Saleh Mahdi; Saadi Mohammed Hilal; Mohammed Redha Annon (Al-Qadisiyah Journal of Pure Science, 2018)
The present search include the recognize the efficiency of pasitoid C. sesamiae on control the larvae of Tarucus rosacea in farm to period from May/2013 until April/2014, this parasitoid discern that infected all the larval stages of the host but in disparate issues. The highest number of parasitoid on the 3rd larval instar (73), while the lowest number on the 1st larval instar (8). The highest parasitism percent will be at November 2013 reach to (63.15%) on 3rd larval instar, while the lowest average of parasitism in the same month at the 1st larval instar (14.28%).The females of parasitoid appear its ability to recognize between the infected and non infected larvae of the host in farm from laying one egg only per larva.